'Redemption Song': Slavery's Disruption in Amos Tutuola's My Life in the Bush of Ghosts. Issue 2 (2nd July 2016) - Jay Lynn, Thomas
Abstract : Slavery is practiced throughout the realm of ghosts in Amos Tutuola's novel, My Life in the Bush of Ghosts, and raises the question as to whether its presence in this realm is fully human. Slavery is presented in certain respects as an anti-human aberration: not only do the ghosts themselves implement varied forms of slavery, but also, at the climactic moment in the human realm, it is music, with its numerous humane associations, that possesses the power to surmount the vices associated with slavery. Tutuola's hero-narrator deploys a childhood song to reach past the defenses of his slaveholding brother's consciousness; the song locates in the brother not just the memory of his childhood with the narrator but also the deep love that imbues their bond. Accessing the liberating potential of human art and love, the narrator-hero touches in this way the brother he had known and ends his own enslavement. Tutuola does not assert, however, that family ties and the renewal of love alone will bring about a more general collapse of the hatred and profiteering that coalesce in slavery. Perhaps the sobering legacy of slavery in West Africa and beyond discourages him from expanding the redemption of one family into a more utopian representation of the end of slavery – or even of the older brother's renunciation of his slave ownership.